(3eYOdGJ Gdfeh (B- (3Jbjje eSJhi Gdfeh GdHOfj (B- (3GdJeGKd (B- (3GdJfGSH GdLSejs - (3MSf Rcj eMeO eMeOs ((3GdGScfOQjIs (3GdecJHI GdeUQjI ddWHGYI hGdfTQ h GdJhRjYs, 2004)
(3Ef GdXhGgQ GdehQa hdLjI GdMjhjI JYJHQ HeKGHI UdGMjGJ CSGSjI ddhUhd Edi GdeSJhjGJ GdYGdjI MjK jTjQ Pdc Cf GdYdGbI Hjf GdUdGMjGJ GdJj jMJGLgG GdfTGW GdQjGVj GdeYjf h eSJhi GdCOGA YdGbI WQOjI cd jDKQ h jJCKQ HGdBNQ (B. (3hGdcQI GdWGFQI ceKGd JWHjbj ef GdCdYGH GdLeGYjI GdJj JJejR HWGHY NGU Yf HGbj GdCdYGH GdLeGYjI GdCNQi(B.s
Keywords: (3GdGdYGH GdLeGYjIs; (3LSe GdGfSGfs